Belief in Treatment as Prevention and Its Relationship to HIV Status and Behavioral Risk. (1st January 2018) - Card, Kiffer G.; Armstrong, Heather L.; Lachowsky, Nathan J.; Cui, Zishan; Sereda, Paul; Carter, Allison; Montaner, Julio S. G.; Hogg, Robert S.; Roth, Eric A.; Moore, David M.
Abstract : Background: We evaluated attitudes toward treatment as prevention (TasP) among gay, bisexual, and other men who have sex with men (GBM) in Vancouver, Canada. Methods: Sexually active GBM, aged ≥16 years, were recruited between 2012 and 2015 using respondent-driven sampling. At each 6-month follow-up, participants completed a computer-administered questionnaire and nursing visit. Repeated-measures latent class analysis, grouped by self-reported serostatus, identified patterns of TasP endorsement by considering TasP-related awareness, attitudes, and behavior. Binary logistic regression identified covariates of class membership. Bivariate interactions with visit number identified factors associated with longitudinal changes in class membership. Results: A total of 774 men provided 2590 observations. Of these, 698 enrolled in the cohort, 575 had at least 1 follow-up visit. Among these, the median follow-up time was 1.98 years (Q1 –Q2 : 1.49–2.49 years). Repeated-measures latent class analysis identified 3 classes: "unaware" (64.2% HIV negative/unknown vs. 29.2% of HIV positive), "skeptical" (29.7% vs. 23.1%), and "believing" (6.1% vs. 47.7%). Membership in classes representing higher TasP endorsement was associated with greater odds of condomless anal sex and having more sexual partners. Age, sexual orientation, ethnicity, substance use, and social time spent with other GBM were also associated with class membership. Longitudinally, class membership was stable among HIV-positive men but shifted toward greater TasP endorsement among HIV-negative/unknown men. For HIV-negative/unknown men, increasing endorsement was positively associated with greater education, being employed, being in a relationship, and substance use and inversely associated with recent serodiscordant condomless anal sex or sexually transmitted infection diagnosis. Conclusions: Over time, disparities in TasP diffusion by HIV status have lessened, although continue to persist across other key social strata. Abstract : Supplemental Digital Content is Available in the Text.